2014
DOI: 10.1260/1756-8277.6.2.163
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of the Curvature Term in the Flame Surface Density Transport Equation: A Direct Numerical Simulations Based Analysis

Abstract: A simple chemistry based three-dimensional Direct Numerical Simulations (DNS) database of freely propagating statistically planar turbulent premixed flames with a range of different values of Karlovitz number Ka, turbulent Reynolds number Re t , heat release parameter τ and global Lewis number Le has been used for the modelling of the curvature term of the generalised Flame Surface Density (FSD) transport equation in the context of Reynolds Averaged Navier Stokes (RANS) simulations. The curvature term has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…The influence of curvature on the displacement speed can be considered through a Markstein length, which should depend on the Lewis number, allowing to take into account differential diffusion. From these observations and the study by Han and Huh [34], which were confirmed by several studies such as [35][36][37], Katragadda et al [38] proposed a model for the stretch due to curvature for flames in the TRZ regime. This model presents some encouraging results allowing to reproduce this stretch for different turbulent intensities.…”
Section: Introductionsupporting
confidence: 67%
See 4 more Smart Citations
“…The influence of curvature on the displacement speed can be considered through a Markstein length, which should depend on the Lewis number, allowing to take into account differential diffusion. From these observations and the study by Han and Huh [34], which were confirmed by several studies such as [35][36][37], Katragadda et al [38] proposed a model for the stretch due to curvature for flames in the TRZ regime. This model presents some encouraging results allowing to reproduce this stretch for different turbulent intensities.…”
Section: Introductionsupporting
confidence: 67%
“…Models for ρS d and S d κ , see Eq. ( 49) and (38), are obtained by integration of the proposed expression of S d , Eq. ( 28), over curvature, using a presumed Gaussian PDF for curvature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations